Qualitative analysis of the implementation of a hospital room service in a large metropolitan hospital: foundations for transformation. Issue 3 (25th September 2022) - Wilkinson, Shelley A.; Bell, Jack J.; Neaves, Bianca; McCray, Sally J.; Campbell, Katrina
ABSTRACT: Introduction and aims: Room service is a hospital meal service model with demonstrated improved nutrition intake, reduced wastage and cost benefits in some settings compared with traditional models. However, uptake across public hospital settings appears low; the underlying reasons require exploration. In 2019, room service was introduced in a Queensland Hospital and Health Service site. The aim of this article is to identify the barriers and enablers to implementing room service to provide recommendations for future implementation of this model. Methods: The current qualitative descriptive study utilized semistructured interviews with project members and key stakeholders involved in implementation of the room service meal delivery model at the Prince Charles Hospital (Queensland, Australia). A convenience sample of participants were recruited. Interviews explored project experiences from commencement to completion, barriers and enablers to implementation, strategies to overcome challenges and recommendations for implementation at other sites. Interviews were coded to identify themes and subthemes. Results: Nine participants were interviewed. Key themes with associated subthemes were (1) foundations of transformation, (2) navigating implementation and (3) embedding sustainable practices. Conclusion: The current study adds rich information to understand factors that support the implementation of a room service model in a large public hospital. Future implementation of room service should not only consider measuring quantifiable outcomes, but also the importance of qualitative descriptive studies surveying project members and key stakeholders to further explore experiences, barriers and enablers to implementation and develop strategies to overcome challenges to assist further sites implement this model.